INHERITANCE OF FERTILITY RESTORATION INVOLVING WILD ABORTIVE CYTOPLASMIC MALE STERILITY SYSTEM IN RICE (Oryza sativa L.) - Hasan, M. J.; Kulsum, M. U.; Ansari, A.; Paul, A. K.; Biswas, P. L. (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Inheritance of fertility restoration was studied in crosses involving ten elite restorer lines of rice viz. BR6839-41-5-1R, BR7013-62-1-1R, BR7011-37-1-2R, BR10R, BR11R, BR12R, BR13R, BR14R, BR15R and BR16R and one male sterile line Jin23A with WA sources of cytoplasmic male sterility. The segregation pattern for pollen fertility of F2 and BC1 populations of crosses involving Jin23A indicated the presence of two independent dominant fertility restoring genes. The mode of action of the two genes varied in different crosses revealing three types of interaction, i.e. epistasis with dominant gene action, epistasis with recessive gene action, and epistasis with incomplete dominance. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16997